Preparation and Characterization of Silver Nanoparticles in Montmorillonite and Gelatin Using Physical and Chemical Methods - Darroudi, Majid (2011)
Metal nanoparticles in inorganic and organic materials have generated novel materials that display unique optical, catalysis, or biological properties making them attractive for using in various application areas. A big challenge in the synthesis of nanoparticles is particle aggregation or precipitation. This phenomenon can be inhibited with stabilization of nanoparticles by suitable polymers or chemical species as colloidal stabilizers. This thesis describes the different preparation methods and characterization of silver nanoparticles (Ag-NPs) in organic and inorganic materials as well as their potential applications. The methods used consist of green chemical method and physical methods, e.g., UV irradiation, pulsed laser ablation (PLA), and y-irradiation. Silver nitrate, montmorillonite (MMT), gelatin, glucose, NaOH, and silver plate were used as starting materials in this work. In UV irradiation method, Ag-NPs were prepared at different irradiation times (i.e., 1, 3, 18, 48, and 96 hr) in MMT and gelatin (i.e., 1, 3, 6, 18, 24, and 48 hr) as inorganic and organic matrix, respectively. UV-vis spectra and transmission electron microscopy (TEM) images demonstrate the particles size of Ag-NPs decrease with the increase of UV irradiation time. In y-irradiation method, when the irradiation dose was increased (from 5 to 50 kGy); the mean size of particles reduced continuously (from 20.4 to 16.4 nm) due to the y-induced Ag-NPs fragmentation. In PLA technique it was found smaller particle size distributions of Ag-NPs were obtained with smaller repetition rates and longer laser ablation times. Also, the UV-vis and TEM images demonstrated that the mean diameter of Ag-NPs increased (from 8.9 to 14.7 nm) as the laser repetition rate was increased (from 10 to 40 Hz). The use of inexpensive chemicals and non-toxic solvents – environmentally friendly and renewable/biodegradable – are central to materials synthesis. The green chemistry rules were applied for preparation of Ag-NPs in gelatin using glucose as a reducing agent,where the particle diameters of Ag-NPs at different temperatures and reaction times were investigated. It was found that with increasing of reaction times (from 6 to 48 hr) the size of Ag-NPs decreased (from 9.6 to 5.3 nm). The particle size of Ag-NPs obtained in gelatin solutions (3.7 nm) is smaller than in gelatin-glucose solutions (5.3 nm) which can be related to rate of reduction reaction. The stability of prepared Ag-NPs, as shown by UV-vis spectral analysis, was significant. The obtained Ag-NPs were characterized by X-ray diffraction (XRD) and atomic force microscopy (AFM). In addition, the Ag-NPs prepared in this work may have value for the creation of antibacterial and antimicrobial paints and coatings for household materials, surgical and food storage equipments.